Performance evaluation of ADMC-MAC mission critical protocol for wireless sensor networks. (17th November 2019) - Sakya, Gayatri; Sharma, Vidushi
Abstract: Mission-critical MAC protocol is an attractive research area since past few years as the wireless sensor networks have developed their utility in mission-critical applications like border surveillance, Tsunami alert systems, and earthquake safety systems, fire fighting applications, industrial automation, pipeline leakage detection system, critical health monitoring, etc. The Wireless sensor networks are deployed for this purpose may be termed as Mission-critical wireless sensor networks, and MAC protocols designed are termed as Mission Critical MAC Protocols for WSN. ADMC-MAC protocol is one of these latest developed protocols. In previous work, the protocol is tested for 40% duty cycle. This paper does the performance evaluation of this protocol in NS-2.35 for different missioncritical scenarios at different duty cycles for mission-critical performance parameters where the actual novelty lies. The results show that the proposed protocol gives best performance when set at 40% duty cycle. It is adaptive to the mission-critical applications and maintains the mission-critical data transport performance along with the energy of the wireless sensor networks. Simulation results confirm that ADMC-MAC model can further be enhanced to reduce data processing delay and for improving data delivery performance. The model may be enhanced by including intelligent nodes only for analyzing and data processing to reduce processing delay .The enhanced model suggested may be used for Mission-critical Wireless Sensor networks in integration with IoT for quick actions in mission-critical application.